Clitic Combinations, Their Hosts and Their Ordering - Terzi, Arhonto (Natural language and linguistic theory, 1999)
In this work we investigate the implications of Kayne's (1994) antisymmetry proposals for the position to which clitics adjoin in the sentence and the manner in which two (or more) clitics may combine. It is demonstrated that adjunction of clitics to${\rm Agr}^{0}$is excluded by antisymmetry, leading to results in the spirit of Chomsky (1995), who dispenses with the notion of agreement as a functional head, hence as a potential adjunction site for clitics. Assuming that the Linear Correspondence Axiom does not apply after spell-out, we argue that${\rm T}^{0}$serves as a host of clitics when Tense features are weak; as for the remaining contexts, we propose that clitics adjoin to heads that are placeholders, departing from the idea that there is a designated functional head and that clitics adjoin to it in all syntactic environments. We present evidence from Greek dialects which supports these claims and instantiates the different manner in which clitics combine in clusters. We extend our proposals to explain similar issues pertaining to the clitic system of the Standard Romance languages.